Effects of hammermills and roller mills on growth performance, nutrient digestibility, And stomach morphology in finishing pigs - Wondra, K.J.; Stark, C.R.; Hines, Robert H.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effects of particle size and mill type used to grind corn were determined with 128 pigs (122 lb average initial body wt). Treatments were corn ground in a hammermill and a roller mill to 800 and 400 μm. The roller mill was more efficient than the hammermill when grinding the corn, with less energy consumption and greater production rate per horsepower hour. For the 800 μm treatments, greater uniformity of particle size was achieved with the roller mill than the hammermill; however, at the 400 μm treatments, corn ground with the hammermill was slightly more uniform. Pigs fed corn ground to 400 μm had 7% greater efficiency of gain, and had greater digestibilities of dry matter, nitrogen, and energy than pigs fed corn ground to 800 μm. Mill type did not affect growth performance, but pigs fed corn ground in the roller mill had greater digestibilities of dry matter, nitrogen, and energy and excreted 18% less dry matter and 13% less nitrogen as feces than pigs fed corn ground in a hammermill. There were interactions among mill type and particle size, with digestibilities much greater for the diet with corn ground to 800 μm in the roller mill compared to the hammermill, but only small advantages in nutrient digestibility for diets with corn ground to 400 μm in the roller mill. Mill type did not affect rate or efficiency of gain, but pigs fed diets with roller-milled corn had greater digestibilities of nutrients and, thus, lower excretions of nutrients in feces.
Keywords: Swine; Finishing; Process; Roller mill